Ethics in sports administration from a documentary perspective - Cabezas Mejía, Edison Damián; Nasimba Suntaxi, Cristina Maribel; Cabezas Mejía, Manuelita; Torres Santamaría, Johana (mktDESCUBRE, 2020)
This article presents a critique of the reality of the sports organizations of our country, who serve as sports administrators; Therein lies the importance of analyzing dimensions such as: ethics, morality, sports administration, leadership, management and other necessary elements that must necessarily know, dominate and apply, to be recognized as leaders who aim to achieve organizational objectives. . The method used was a review of the academic literature, that is, a documentary-type investigation, a level of descriptive study and its approach was, the qualitative one; because he sought to understand and interpret reality, to analyze and interpret it and then explain it. Ethics cannot be separated from the administrative actions of the sports leader, personal and professional; because if we want an inspiring, visionary leader that leads to the achievement of quality standards; this sports manager must be and seem.